Loss of Fmr1 reorganizes the multi-elemental composition across tissues in Fragile X Syndrome mice - Sabiha Alam; Jamie T. Reeves; Shawn M. Wilder; Elizabeth A. McCullagh (PLoS ONE, 2026)
Fragile X Syndrome (FXS) results from a genetic mutation which silences the expression of Fragile X Messenger Ribonucleoprotein (FMRP). FMRP serves various roles regulating cellular protein synthesis including mRNAs that code for proteins regulating ion flux. However, there are few studies measuring the elemental balance between FXS genotypes and tissues. Here, we measured the multivariate balance of 10 elements in tissues of wild-type and Fmr1-knockout mice to compare elemental composition of brain and somatic tissues within and across genotypes. Using a Bayesian mixed model approach, we found that the main differences between groups were between tissues, with significant effects of genotype and interaction of tissue on genotype. Wild-type feces were significantly higher in magnesium and sodium than knockout. Fur was significantly higher in potassium in wild-type, which was supported by the interaction effect of genotype with tissue. These results align with previous work showing FXS pathologies alter electrolytic and metal ion regulation, neuronal excitability, and gastrointestinal function. Future work should additionally test how elemental differences relate to function at the cellular level, as well as patterns of individual intake, digestion, assimilation, and/or excretion.